On Callavia (Trilobita) from the Cambrian Series 2 of Iberia with systematic status of the genus. (November 2021) - Collantes, Luis; Pereira, Sofia; Mayoral, Eduardo; Liñán, Eladio; Gozalo, Rodolfo
Abstract: Olenellid trilobites from the lower Cambrian of the Iberian Peninsula are very scarce and poorly studied, making them difficult to compare with defined species and to include in biostratigraphic and paleobiogeographic analyses. Based on newly collected specimens, we revise the species ' Callavia ? lotzei ' Richter and Richter, 1941 from the 'Cumbres beds' of Cumbres de San Bartolomé and the 'Herrerías shale' of Cañaveral de León, Sierra del Bujo, and Hinojales (Huelva, Spain), and ' Paradoxides choffati ' Delgado, 1904 from the Vila Boim Formation of Elvas (Portugal). The new material indicates that Callavia ? lotzei is a junior synonym of ' P. choffati .' The Iberian species are here assigned to Callavia Matthew, 1897, for which morphological characters are reassessed, offering a valuable opportunity to discuss characters previously misinterpreted for this genus. Traditionally assigned to the Olenelloidea Walcott, 1890, Callavia lacks some of the diagnostic characters of this superfamily and is here assigned to Judomioidea Repina, 1979 . A new diagnosis for this genus is provided, and Sdzuyomia Lieberman, 2001 is considered to represent a junior synonym of Callavia . The genus Callavia is distributed across the western margin of Gondwana, from the western Mediterranean region (Iberia and Morocco) throughout all the Avalonia sectors (UK, eastern Newfoundland, and Massachusetts). Its presence in Iberia supports the faunal links between the West Gondwana domain and Avalonia during Cambrian Series 2. The Iberian records of Callavia choffati are assigned to the middle part of the regional Marianian Stage (uppermost Cambrian Stage 3 to the lowermost Cambrian Stage 4) and correlates with the Callavia Biozone of Avalonia (lower Branchian Series).